2016
DOI: 10.1080/09540121.2016.1226477
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviors among women living with HIV in Ontario, Canada

Abstract: Understanding the sexual activities and partnerships of women living with human immunodeficiency virus (HIV) remains important to promote healthy sexuality and to reduce the transmission of HIV and other sexually transmitted infections. We described sexual behaviors of women living with HIV enrolled in an ongoing study in Ontario, Canada. Data were available from 582 women who self-completed a sexual behavior questionnaire between 2010 and 2012. Nearly half (46.1%) of women reported a sexual partner in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In total, 32 quantitative studies involving 11,552 women living with HIV were included in our review (Agaba et al, 2017;Bernier et al, 2016;Bogart et al, 2006;Bouhnik et al, 2008;Castro, Le Gall, Andreo, & Spire, 2010;Florence et al, 2004;Kaida et al, 2015;Luzi et al, 2009;Robinson et al, 2017;Schrooten et al, 2001;Taylor et al, 2015;Trotta et al, 2008;Valadares et al, 2014;Wessman et al, 2015;Wilson et al, 2010;Zierler et al, 1999). Henceforth, for clarity, we have identified them by their alphabetically assigned number in the reference list.…”
Section: Critical Review Of Past Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 32 quantitative studies involving 11,552 women living with HIV were included in our review (Agaba et al, 2017;Bernier et al, 2016;Bogart et al, 2006;Bouhnik et al, 2008;Castro, Le Gall, Andreo, & Spire, 2010;Florence et al, 2004;Kaida et al, 2015;Luzi et al, 2009;Robinson et al, 2017;Schrooten et al, 2001;Taylor et al, 2015;Trotta et al, 2008;Valadares et al, 2014;Wessman et al, 2015;Wilson et al, 2010;Zierler et al, 1999). Henceforth, for clarity, we have identified them by their alphabetically assigned number in the reference list.…”
Section: Critical Review Of Past Researchmentioning
confidence: 99%
“…In much of the literature, investigators provided no definition of sexual activity at all, leading readers to assume that it meant heterosexual (penile-vaginal) intercourse. When definitions were provided, they were most often restricted to interpersonal sex involving vaginal and anal intercourse (3,22,27), and, in two cases, oral sex as well (16,24). Two studies also counted caressing and foreplay (10,31) and just one reported on self-pleasure among women (14).…”
Section: Quantitative Conceptualizations Of Sexualitymentioning
confidence: 99%
See 3 more Smart Citations